Usabilidade de ambientes de gestão de aprendizagem: uma análise comparativa - Simões, Guilherme Campos (2008)
The research objective is to present a general approach about Distance Learning and Learning Management Systems (LMS), followed by a vision about interface usability and software evaluation. Two LMS be presented: Moodle and TelEduc. These two environments are evaluated for usability through questionnaires and based on data collected was observed that for most of usability heuristics the Moodle users were more satisfied. It also noted that users of the two environments have in common the fact of consider the weakest point of environments the occurrence of errors and an ineffective error prevention.